10 years of the Belt and Road Initiative (BRI) as a global infrastructure development and international cooperation strategy promoted by the People's Republic of China - Valdiglesias Oviedo, Jhon (2024)
The purpose of this study is to examine trends in Chinese investment within the context of the Belt and Road Initiative (BRI) and to recognize the opportunities that arise for Latin America. To this end, the literature summarizing the relations between these two economies was compiled. In addition, various sources of information were used to evaluate Chinese projects in different regions and compare them with those in Latin America. The results confirm China's strong dynamism, although recently softened by greater adversity to irrigation. At the same time, there is an important momentum with some large investments in the region, especially in South America. It is concluded that the region has favorable conditions to capitalize on the opportunities generated by the IFR.